2005
DOI: 10.1088/0954-3899/31/7/006
|View full text |Cite
|
Sign up to set email alerts
|

Prospect of determining the Dirac/Majorana state of the neutrino by a Multi-OWL experiment

Abstract: We consider the non-radiative two body decay of a neutrino to a daughter neutrino with degraded energy and a very light particle (Majoron). Ultrahigh energy neutrinos from an astrophysical source like a Gamma Ray Burst undergoing this decay process are found to produce different number of events in the detector depending on whether they are Majorana or Dirac particles. The next generation large scale experiments like Multi-OWL is expected to provide us an accurate determination of the flux of neutrinos from as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…AGN, if they produce measurable fluxes of neutrinos, would provide a range of very remote point sources. Measurements of neutrinos from a variety of distances (ideally with flavor ratios) would provide important information for testing neutrino properties at increas-ing L/E (distance/energy) [22,92,93,94,95,96,97,98,99,100].…”
Section: A Tev Neutrino Beaconmentioning
confidence: 99%
“…AGN, if they produce measurable fluxes of neutrinos, would provide a range of very remote point sources. Measurements of neutrinos from a variety of distances (ideally with flavor ratios) would provide important information for testing neutrino properties at increas-ing L/E (distance/energy) [22,92,93,94,95,96,97,98,99,100].…”
Section: A Tev Neutrino Beaconmentioning
confidence: 99%
“…Indeed, neutrinoless double-beta decay proceeds only when neutrinos are massive Majorana particles, hence its observation would resolve the question [28]. It has been shown that the inclusion of the np pairing a e-mail: allaln@yahoo.com influences the neutrinoless double-beta decay rates significantly [9].…”
Section: Introductionmentioning
confidence: 99%